2016
DOI: 10.1530/eje-16-0286
|View full text |Cite
|
Sign up to set email alerts
|

Exenatide improves β-cell function up to 3 years of treatment in patients with type 2 diabetes: a randomised controlled trial

Abstract: Objective: Glucagon-like peptide (GLP)-1 receptor agonist treatment improves β-cell function. In this study, we investigated whether the improvements are sustained during a 3-year treatment period. Research design and methods: Sixty-nine metformin-treated type 2 diabetes patients were randomised to the GLP1 receptor agonist, exenatide (EXE) twice daily (BID) or to insulin glargine (GLAR). β-cell function parameters were derived using the Mari model from standardised breakfast and lunch meals that were administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…Thus, the importance of preserving β‐cell function and improving insulin resistance in the management of T2DM is highlighted. Our results were consistent with several large clinical trials assessing GLP‐1RAs and DPP‐4Is separately . In one trial specifically designed to determine the effect on β‐cell function, exenatide, a GLP‐1 receptor agonist, was demonstrated to improve β‐cell function, as measured not only by static index (HOMA‐B, fasting C‐peptide), but also by dynamic tests (hyperglycaemic clamps), and the favourable effect was sustained for up to 3 years .…”
Section: Discussionsupporting
confidence: 88%
“…Thus, the importance of preserving β‐cell function and improving insulin resistance in the management of T2DM is highlighted. Our results were consistent with several large clinical trials assessing GLP‐1RAs and DPP‐4Is separately . In one trial specifically designed to determine the effect on β‐cell function, exenatide, a GLP‐1 receptor agonist, was demonstrated to improve β‐cell function, as measured not only by static index (HOMA‐B, fasting C‐peptide), but also by dynamic tests (hyperglycaemic clamps), and the favourable effect was sustained for up to 3 years .…”
Section: Discussionsupporting
confidence: 88%
“…[78][79][80] In a head-to-head study with the sulfonylurea glipizide, the SGLT-2 inhibitor dapagliflozin had a lower initial effect on HbA1c reduction (−0.4% vs −0.8%); however, the reduction in glucose levels was more sustained over time with dapagliflozin, resulting in a 0.3% benefit at 208 weeks. 29 Interestingly, the improvement in beta-cell function parameters was sustained during the 3-year treatment period in the 52% of originally randomized patients who completed this small study ( Figure 1D). 84 In addition, reduced appetite limits the size of the ingested meal.…”
Section: Sglt-2 Inhibitionmentioning
confidence: 84%
“…81 production and glucagon secretion. 29 85 All these factors result in reduced postprandial glucose, and thus insulin levels.…”
Section: Sglt-2 Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large body of clinical research has demonstrated that GLP-1-based drugs provide excellent control of blood glucose levels without dramatic side effects [1214]. Furthermore, GLP-1 analogs can improve β-cell function, especially in regards to insulin secretion and glucose sensitivity, while promoting β-cell survival by inhibiting apoptosis and enhancing cell proliferation [3, 15, 16]. Six GLP-1 analogs are commercially available as monotherapies for T2DM and are divided into shorting-acting exenatide and lixisenatide, long-acting liraglutide and prolonged-acting exenatide LAR, albiglutide and dulaglutide, based on the duration of action and frequency of injection [3].…”
Section: Discussionmentioning
confidence: 99%